Experimental study of thermoelectric cooler for diode pumped solid state laser - Wan Razali, Wan Aizuddin; Bidin, Noriah; Saidin, Mohamad Khairi (Faculty of Science, University Teknologi Malaysia, 2006)

(untitled)
Thermoelectric cooler (tec) is a solid state heat pump. It normally used for a diode pumped solid state (dpss) laser. It is used to control and stabilize the temperature of pumping source of laser diode (ld) and the frequency doubled of kalium titanyl phosphate (ktp) crystal. The aim of this study is to diagnose the performance of tec in dpss system. High power laser diode driver circuit was utilized as a pumping source. The current of the driver circuit was verified and the temperature of the ld and ktp were measured. The result obtained indicates that, the temperature of ld linearly increased upon the current in the initial stage. After achieving a threshold current of 7 a the temperature remained constant at 25.4 oc. Unlike in ktp crystal, initially the temperature was nonlinearly decreased down to the minimum of 14.8 oc at threshold current. The temperature was then nonlinearly increased up to maximum of 25.7 oc at 15 a. Beyond 18 a, the temperature slightly dropped and remained constant at the same value of ld temperature of 25.4 oc. Hence the tec was stabilized and controlled the temperature of dpss laser at 25.4 oc. The best performed of tec when the pumping current exceeds 18 a